Pengaruh Phubbing Terhadap Prokrastinasi Akademik Siswa Kelas X di SMAN 6 Kota Bogor - Khairun Nisa; Rusdi Kasman; Hafiz Taqwa (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
Current technological advances have had a significant impact, particularly on developments in education. But in its development, of course, the world of education will never be separated from a problem. This study aims to determine whether there is an effect of phubbing on the academic procrastination of high school students. This study used a quantitative approach using regression research methods. The subject of this study is high school students. The population in this study was 317 students of SMAN 6 Bogor City. The simple random sampling technique was used to determine sampling and was obtained by 76 students based on Slovin's counting technique. The research data were analyzed through a simple linear regression test. Research results show that there is a significant effect of phubbing behavior on student academic procrastination (sig<0.05) with a coefficient of determination of 13.4%. This value can be interpreted as meaning that the phubbing variable has an influence of 13.4% on the academic procrastination of grade X students at SMAN 6 Bogor City, while the remaining 86.6% of students' academic procrastination is influenced by other variables outside this study. A regression coefficient value of 0.380 indicates that every single unit increase in the phubbing variable, the academic procrastination score tends to increase by 0.380. This can be concluded that the higher the student phubbing, the higher the student's academic procrastination. On the other hand, the lower the phubbing, the lower the academic procrastination of students.